If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2.5x + 5 = 3x Reorder the terms: 5 + 2.5x = 3x Solving 5 + 2.5x = 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 5 + 2.5x + -3x = 3x + -3x Combine like terms: 2.5x + -3x = -0.5x 5 + -0.5x = 3x + -3x Combine like terms: 3x + -3x = 0 5 + -0.5x = 0 Add '-5' to each side of the equation. 5 + -5 + -0.5x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -0.5x = 0 + -5 -0.5x = 0 + -5 Combine like terms: 0 + -5 = -5 -0.5x = -5 Divide each side by '-0.5'. x = 10 Simplifying x = 10
| 625=53x+1 | | .75x-2=28 | | -189-x+12x=53 | | 2x(.333)+1=11 | | (8x)+(2y)=36 | | 10-.5x=7.5 | | f(x)=x^3-x-1 | | .333x+5=13 | | 14-x=30 | | -4x+12=x^2 | | .5x+3=97 | | 10=2/3/h | | -12x+3x-168=93 | | 2x-3y=29 | | (X+2)(X+1)=(X+1)(-X+3) | | 4x+2=5-3x | | log(x+4)+log(x-2)=4 | | 4x-(2x+6)=20 | | 151x+47y+16z=2124 | | 50-13.28=9x | | (X+1)+6=0 | | -2x+8x-42=66 | | F(x)=-3X^3-2x+4 | | 9x-25=8x-25 | | 20=-5v-5 | | 3w+12=66 | | (k-2)x+(k+4)y+3k^2-8k+5=0 | | 3(x+6)=4x+8 | | abs(5x-4)=abs(3x+6) | | 7x-105+6x=155 | | ((5+(1*(1*(60-43))))-14)*5= | | X^4-5x^3+8x-5x+1=0 |